Cognitive Science in the Study of Early Christianity: Why It Is Helpful - and How? - Uro, Risto (New Testament studies, 2017)
In recent years, a number of New Testament and early Christian scholars have begun to use cognitive science approaches in their work. In this paper, I situate those efforts within the larger framework of the changing humanities, and the increased interest among humanistic scholars and social scientists in drawing on the growing body of knowledge on the cognitive and evolutionary roots of human thinking and behaviour. I also suggest how cognitive historiography can be helpful in shedding new light on issues discussed by New Testament scholars, by elaborating a case study: an analysis of the rite introduced by John the Baptist.